Synthesis, Structure, Photoluminescent and Semiconductor Properties of, and Theoretical Calculations for, a Novel Zinc Complex. (October 2017) - Yi, Xiu-Guang; Chen, Wen-Tong; Huang, Jian-Gen; Zhang, Ding-Wa; Wang, Yin-Feng
A novel zinc complex [Zn3 (2, 2′-bi-1H-imidazole)2 (1H-biimidazole)2 (SO4 )2 ] n has been synthesised through a solvothermal reaction and structurally characterised by single-crystal X-ray diffraction. It has a one-dimensional chain-like structure with both tetrahedral and square pyramidal zinc atoms. A three-dimensional supramolecular framework is constructed through hydrogen-bonding interactions. Photoluminescence shows that the complex displays an emission in the blue region of the light spectrum that time-dependent density functional theory calculations reveal can be attributed to ligand-to-ligand charge transfer. Solid-state diffuse reflectance measurements show the existence of a narrow optical band gap of 2.08 eV.